Effect of sodium bicarbonate supplementation on 2000-m rowing performance - Hobson, R. M.; Harris, R. C.; Martin, D.; Smith, P.; Macklin, B.; Elliot-Sale, K. J.; Sale, C. (International Journal of Sports Physiology and Performance, 2014)
The ability to buffer H+ could be vital to exercise performance, as high concentrations of H+ contribute to the development of fatigue. Purpose: The authors examined the effect of sodium bicarbonate (SB) supplementation on 2000-m rowing-ergometer performance. Methods: Twenty male rowers (age 23 ± 4 y, height 1.85 ± 0.08 m, mass 82.5 ± 8.9 kg, 2000-m personal-best time 409 ± 16 s) completed two 2000-m rowing-ergometer time trials, separated by 48 h. Participants were supplemented before exercise with 0.3 g/kg body mass of SB or a placebo (maltodextrin; PLA). The trials were conducted using a double-blinded, randomized, counterbalanced crossover study design. Time to complete the 2000-m and time taken for each 500-m split were recorded. Blood lactate, bicarbonate, pH, and base excess were determined preexercise, immediately postexercise, and 5 min postexercise. Performance data were analyzed using paired t tests, as well as magnitude-based inferences; hematological data were analyzed using a repeated-measures ANOVA. Results: Using paired t tests, there was no benefit of SB over PLA (P = .095). However, using magnitude-based inferences there was a likely beneficial effect of SB compared with PLA (PLA 412.0 ± 15.1 s, SB 410.7 ± 14.9 s). Furthermore, SB was 0.5 ± 1.2 s faster than PLA in the third 500 m (P = .035; possibly beneficial) and 1.1 ± 1.7 s faster in the fourth 500 m (P = .004; very likely beneficial). All hematological data were different between SB and PLA and were different from preexercise to postexercise. Conclusion: SB supplementation is likely to be beneficial to the performance of those competing in 2000-m rowing events, particularly in the second half of the event.